Integrating Artificial Intelligence (AI) Into Technical and Vocational Education and Training (TVET): A Prisma-Based Systematic Review - Beri̇gel, Duygu Solak; Şilbir, Lokman; Şilbir, Gülbahar Merve (Calitatea Vieții, 2025)
In today's world, characterized by the dominance of digital technologies, vocational education plays a pivotal role in driving economic growth and development. Nevertheless, it faces significant challenges in adapting to the rapidly evolving demands of modern industries. This study explores the role of Artificial Intelligence (AI) in reshaping vocational education curricula. A total of 73 articles were initially identified from the Web of Science database using specific queries related to AI, vocational education, and curriculum design. After applying inclusion and exclusion criteria, 27 articles published between 2019 and 2024 were selected for in-depth analysis. The systematic review employs the PRISMA methodology to analyze 73 articles, ultimately focusing on 27 relevant studies published between 2019 and 2024. The systematic review in the study follows the PRISMA methodology, ensuring a rigorous and transparent process. Key themes include the integration of AI tools for data-driven insights, personalized learning environments, curriculum design emphasizing AI and digital skills. The study underscores the importance of AI in enhancing teaching practices, promoting inclusiveness, and preparing students for AI-focused careers. It also emphasizes the necessity of AI training for educators, equitable access to technology, and the development of ethical frameworks to guide AI integration in education. The findings emphasize that personalized learning supported by AI enhances students' skill acquisition and aligns educational outcomes with workforce demands. Legal and ethical dimensions of AI, particularly in vocational education, need to be addressed to ensure responsible usage and equitable implementation.